DEVELOPING AN INNOVATIVE ENGLISH GRAMMAR LEARNING MODULE TO IMPROVE WRITING SKILLS IN JUNIOR HIGH SCHOOLS - Leroy Holman Siahaan; Dini Hidayati; Novi Andriani; Firsta Malyda Putri (University of Kuningan, 2025)
Writing skills play a crucial role in language mastery, requiring a deep understanding of linguistic structures, particularly grammar. In the current junior high school (SMP) curriculum, grammar is integrated into various learning modules, often making students unaware that they are acquiring grammatical concepts. This research aims to develop an innovative grammar learning module to: (1) facilitate students' comprehension of grammatical rules, (2) improve students' writing proficiency with a strong grammatical foundation, (3) evaluate the module’s suitability for junior high school writing instruction, and (4) gather feedback from educators and students on its implementation in Bekasi City schools. Utilizing the Research and Development (R&D) methodology with the 4-D model—definition, design, development, and dissemination—this study employed interviews and questionnaires for data collection. Content, media, and language experts validated the module to ensure its effectiveness. The findings demonstrate that the grammar learning module significantly enhances students' writing skills, as reflected in improved writing test scores and positive feedback from both teachers and students. This research contributes to the advancement of grammar instruction by offering a structured and engaging approach tailored to the needs of junior high school learners. Keywords: learning module; English grammar; writing skills; junior high school students; research and development (R&D)